PERANCANGAN SISTEM TRANSMISI GOKAR LISTRIK - Jerry Rapar Pangayow; Stenly Tangkuman; Michael E Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2016)
The Development of automotive todays is very fast because every single year there is always something new. This research aims to design fuel-efficient vehicles and environmentally friendly, especially the transmission is driven by an electric motor that used a chain sprocket transmission system is applied to the electric gocart. From the results of this research shows that the transmission can be used on a simple electric gocart transmission system chain sprocket is roll type single line, which consists of two sprocket and chain on rotation 1 750 rpm and 2 hp motor power. Dimensions obtained by the small sprocket diameter 35 mm with a number of teeth 9 pieces, large sprocket diameter 250 mm with a number of teeth 62 fruit and chain length of 1,243 mm at a distance of 381 mm spindle axis. Keywords: Design, Transmission Chain, Electric Gocart